KONSEP PENDIDIKAN KARAKTER RELIGIUS KI HADJAR DEWANTARA - Solehah, Siti; Arnadi , Arnadi; Irawan , Deni (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This research aims to analyse the purpose of character education according to Ki Hadjar Dewantara and its relevance to current education. The research uses library research. library research. As for the techniques in This data collection technique uses Data analysis technique with content analysis. The purpose of Ki Hadjar Dewantara's character education is independence, freedom physically and mentally without the existence of a religion. The purpose of Ki Hadjar Dewantara's character education is independence, namely freedom physically and mentally without coercion. coercion. So as to become a human being so that it becomes a whole human being with good character. While the concept education which concerns the principles of nationality, the principles of culture, the principles, the principles of independence, the principles of humanity, the principles of natural nature. humanity, the principle of natural nature. The foundation is tawakal and manunggaling kawula gusti. In the implementation of education, Ki Hadjar Dewantara uses the